Enzymatic Radiofluorination: Current Status - Martarello, L.; Plisson, C.; Gee, A.D. (Current Radiopharmaceuticals, 2010)
This review provides a overview of the use of biocatalysts in fluorine-18 chemistry that have emerged so far. The preparation of the following radiolabelled counpunds are discussed: [18F]5'-FDA, [18F]5'-FDI, [18F]5-FDR using different enzyme combinations. Nethertheless, the major emphasis is placed on the use of a key enzyme (ie the fluorinase) mediating the reaction between the fluoride ion and S-adenosyl-L-methionine (SAM) to yield the natural product 5'- fluoro-5'-deoxyadenosine (5'-FDA) and the subsequent enzymatic conversion of 5'-FDA into 5'-FDI and 5-FDR.
Keywords: 5-FDR